3D thermography in non-destructive testing of composite structures. (19th October 2016) - Hellstein, Piotr; Szwedo, Mariusz
Abstract: The combination of 3D scanners and infrared cameras has lead to the introduction of 3D thermography. Such analysis produces results in the form of three-dimensional thermograms, where the temperatures are mapped on a 3D model reconstruction of the inspected object. All work in the field of 3D thermography focused on its utility in passive thermography inspections. The authors propose a new real-time 3D temperature mapping method, which for the first time can be applied to active thermography analyses. All steps required to utilise 3D thermography are discussed, starting from acquisition of three-dimensional and infrared data, going through image processing and scene reconstruction, finishing with thermal projection and ray-tracing visualisation techniques. The application of the developed method was tested during diagnosis of several industrial composite structures—boats, planes and wind turbine blades.